Antiretroviral therapy (ART) for treating HIV infection in ART-eligible pregnant women - Lomar, André Villela (São Paulo Medical Journal, 2010)
BACKGROUND: This systematic review focuses on antiretroviral therapy (ART) for treating human immunodeficiency virus (HIV) infection in ART-eligible pregnant women. Mother-to-child transmission (MTCT) is the primary means by which children worldwide acquire HIV infection. MTCT occurs during three major timepoints during pregnancy and the postpartum period: in utero, intrapartum, and during breastfeeding. Strategies to reduce MTCT focus on these periods of exposure and include maternal and infant use of ART, caesarean section before onset of labour or rupture of membranes, and complete avoidance of breastfeeding. Where these combined interventions are available, the risk of MTCT is as low as 1-2%. Thus, ART used among mothers who require treatment of HIV for their own health also plays a significant role in decreasing MTCT. OBJECTIVE: Our objective was to assess the current literature regarding the treatment of HIV infection in pregnant women who are clinically or immunologically eligible for ART. This review includes an evaluation of the optimal time to start therapy in relation to the woman’s laboratory parameters and/or gestational age. It also includes an analysis of which specific antiretroviral medications to start in women who are not yet on ART and which agents to continue in women who are already on ART. CRITERIA FOR CONSIDERING STUDIES FOR THIS REVIEW: In June 2009, electronic searches were undertaken in these databases: Cochrane’s “CENTRAL,” EMBASE, PubMed, LILACS, and Web of Science/Web of Social Science. Hand searches were performed of the reference lists of all pertinent reviews and studies identified. Abstracts from relevant conferences were searched. Experts in the field were contacted to locate additional studies. The search strategy was iterative. SELECTION CRITERIA: We selected randomized controlled trials and observational studies that evaluated pregnant women with HIV infection who were eligible for ART according to criteria defined by the WHO guideline review committee. Studies were included in the systematic review when a comparison group was clearly defined and where the intervention comprised triple ART. For a study to be considered, each medication in the ART regimen needed to be clearly described. DATA COLLECTION AND ANALYSIS: Two authors independently assessed the selected studies for relevance and inclusion. Relevant data was then extracted from included studies, and the risk of bias assessed. In each included study, the relative risk (RR) for the intervention versus the comparison group was calculated for each outcome, as appropriate, with 95% confidence intervals (CIs). MAIN RESULTS: To our knowledge, there are no randomized controlled trials or observational studies that address the optimal time to start antiretroviral drugs in ART-eligible pregnant women in relation to the woman’s laboratory parameters and/or gestational age. The medications to continue in ART-eligible pregnant women who are already receiving ART also have not been evaluated systematically in the current literature. The long-term mortality of HIV-positive pregnant women on ART for their own health, and the long-term virologic or clinical efficacy of ART in treating them, has not been evaluated in randomized clinical trials. In this review, surrogate outcomes for long-term mortality and virologic and clinical efficacy (e.g. MTCT and infant HIV transmission or death) were evaluated to determine the efficacy of specific antiretroviral regimens to start in women who are not yet on ART. In June 2009, electronic searches were undertaken in these databases: Cochrane’s “CENTRAL,” EMBASE, PubMed, LILACS, and Web of Science/Web of Social Science. Hand searches were performed of the reference lists of all pertinent reviews and studies identified. Abstracts from relevant conferences were searched. Experts in the field were contacted to locate additional studies. The search strategy was iterative. AUTHORS’ CONCLUSIONS: In ART-eligible pregnant women with HIV infection, ART is a safe and effective means of providing maternal virologic suppression, decreasing infant mortality, and reducing MTCT. Specifically, AZT/3TC/NVP, AZT/3TC/LPV-r, and AZT/3TC/ ABC have been shown to decrease MTCT. More research is needed regarding the use of specific regimens and their maternal and infant side-effect profiles.